The Effect of Internal Inventory Control and Accounting Information Systems on the Prevention of Fraud in Inventory (Study at PT. Astra International Tbk. - Honda NTB Branch) - Maudita Candrayani; Elin Erlina Sasanti (Cita Konsultindo Research Center, 2024)
This study aims to determine the effect of internal inventory control and accounting information systems on the prevention of fraud on inventory at PT Astra International Tbk - Honda NTB Branch. The population in this study were leaders and employees of PT Astra International Tbk - Honda NTB Branch. The technique used for sampling in this study was non-probability sampling with a purposive sampling method so that the number of samples in this study was 60 employees. This study uses statistical tests with the SmartPLS software application. The results of this study indicate that internal inventory control and accounting information systems have a positive and significant effect on fraud prevention in the inventory of PT Astra International Tbk- Honda NTB Branch. The company has carried out internal inventory control effectively and efficiently using the applicable SOP (Standard Operational Procedure). The Accounting Information System has also been carried out as its function is proper and adequate so that it can facilitate the company in storing company data and can facilitate employee work so that fraud prevention can be done correctly.